2007
DOI: 10.1186/1471-2164-8-435
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cyanobacterial superoxide dismutases to discriminate canonical forms

Abstract: Background: Superoxide dismutases (SOD) are ubiquitous metalloenzymes that catalyze the disproportion of superoxide to peroxide and molecular oxygen through alternate oxidation and reduction of their metal ions. In general, SODs are classified into four forms by their catalytic metals namely; FeSOD, MnSOD, Cu/ZnSOD and NiSOD. In addition, a cambialistic form that uses Fe/Mn in its active site also exists. Cyanobacteria, the oxygen evolving photosynthetic prokaryotes, produce reactive oxygen species that can da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 31 publications
5
64
0
Order By: Relevance
“…were found in the cyanobacterial Cu/ ZnSOD protein sequence (Priya et al, 2007), and protein sequences (GFHLHAGDQC and GGGGARIACG) of the Cu/ ZnSOD putative encoding gene (sync_1771, sodC) in Synechococcus 9311 (Palenik et al, 2006) fitted well with them. Combined with in-gel activity staining and immunoblotting results, we concluded that sync_1771 in Synechococcus 9311 encoded Cu/ZnSOD (unpublished data).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…were found in the cyanobacterial Cu/ ZnSOD protein sequence (Priya et al, 2007), and protein sequences (GFHLHAGDQC and GGGGARIACG) of the Cu/ ZnSOD putative encoding gene (sync_1771, sodC) in Synechococcus 9311 (Palenik et al, 2006) fitted well with them. Combined with in-gel activity staining and immunoblotting results, we concluded that sync_1771 in Synechococcus 9311 encoded Cu/ZnSOD (unpublished data).…”
Section: Introductionmentioning
confidence: 68%
“…All cyanobacteria have a cytosolic sod gene encoding either soluble FeSOD or soluble NiSOD, and these could be the housekeeping SODs (Regelsberger et al, 2004;Priya et al, 2007). Some cyanobacteria have additional SODs, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The SODs are a polyphyletic family of metalloproteins, the most common of which contain Fe (FeSODs), Mn (MnSODs), Cu plus Zn (Cu/ZnSODs), or Ni (NiSODs) as active site catalysts. The FeSODs and MnSODs exhibit very similar sequence and structure, reflecting a common ancestry, while the Cu/ ZnSODs and NiSODs are distinct from the FeSODs and MnSODs and from each other (Fink and Scandalios, 2002;Priya et al, 2007). The FeSODs, MnSODs, and Cu/ZnSODs are widely distributed, and organisms typically possess enzymes of more than one class; many cyanobacteria have both FeSODs and MnSODs, metazoa and fungi produce both MnSODs and Cu/ZnSODs, and embryophytes synthesize all three forms (Fink and Scandalios, 2002; reviewed in Grace, 1990;Bowler et al, 1992;Pilon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the amino acid sequences (GenBank: AHH25151) verified the presence of the characteristic N-and C-terminal domains (pfam00081 and pfam02777 respectively). The gene also contained the SOD signature, (Priya et al, 2007).…”
Section: Cloning and Production Of Recombinant S Subrutilus P5 Fesodmentioning
confidence: 99%